2019
DOI: 10.3390/ma13010095
|View full text |Cite
|
Sign up to set email alerts
|

Releasing Behavior of Lipopolysaccharide from Gelatin Modulates Inflammation, Cellular Senescence, and Bone Formation in Critical-Sized Bone Defects in Rat Calvaria

Abstract: Lipopolysaccharide (LPS) is a well-known strong inducer of inflammation. However, there is little information regarding how LPS-release behavior affects cellular senescence at the affected area. In this paper, we demonstrate that a vacuum-heating technique (dehydrothermal treatment) can be utilized to prepare an LPS sustained-release gelatin sponge (LS-G). LPS sustained release from gelatin leads to the long-term existence of senescent cells in critical-sized bone defects in rat calvaria. Three types of gelati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 46 publications
0
19
0
Order By: Relevance
“…LS-Gs containing 12.42 EU/mg of LPS were prepared as reported previously [ 17 ]. Our previous study revealed that LS-G could retain LPS in similar bone defects for at least three weeks.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…LS-Gs containing 12.42 EU/mg of LPS were prepared as reported previously [ 17 ]. Our previous study revealed that LS-G could retain LPS in similar bone defects for at least three weeks.…”
Section: Resultsmentioning
confidence: 99%
“…This discrepancy might be due to the difference in the bonding between LPS and gelatin. Recently, we identified that reagent-grade gelatin contains a small amount of LPS [ 17 ]. We fabricated vacuum-heated gelatin sponges (LS-G) [ 17 ] because dehydrothermal treatment using vacuum heating is known to enhance ester bonding between carboxyl and hydroxyl groups of molecules [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LPS, which is an outer-cell membrane of Gram-negative bacteria, is an established strong stimulant for modulating the immune system and inducing inflammation [ 35 , 36 ], which diverges bone formation that is primarily dependent on its dose and sustained condition to the matrix materials [ 36 , 37 , 38 ]. We have previously reported that even tiny contaminations involving minute amounts of LPS in gelatin sponges remarkably hindered bone formation in a similar bone defect model [ 38 ]. Xu et al also reported that the combined use of the NF-κB activator and gelatin augmented severe inflammation [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…What is already a certainty today is the safety of many of the components of biomaterials and cells (for example, adipose cells) supported by biomaterials in animals (Zhao et al, 2019;Kupikowska-Stobba and Lewińska, 2020;Otake et al, 2020). These results led us to argue that the gap between animals and humans in this context will be closed soon.…”
Section: Future Perspectives/next Stepsmentioning
confidence: 99%